P. Mohyla: bohoslov, cerkovnyj i kulʹturnyj dijač - Kolodnyj, Anatolij Mykolajovyč (Vyd. Chudožnʹoi͏̈ Literatury Dnipro, 1997)
Contains addresses presented at International Academic Conference called "Petro Mohyla i suchasnistʹ" held in Kyi͏̈v in March 1996 under the auspices of the two academies